Solve the post-operative subdural pneumatosis of chronic subdural hematoma: A novel active bone hole drainage system - Zhang, Sheng; Zhang, Xin; Ding, Jian (Frontiers in Neurology, 2022)
Background: Postoperative subdural pneumatosis (PSP) is commonly encountered after the chronic subdural hematoma (CSDH) surgery which currently lacks effective methods to avoid the condition. This study invented an active bone hole drainage system to change the venting technique with the aim of comparing postoperative efficacy and prognosis to traditional drilling and drainage. Methods: We conducted a randomized controlled trial between January 2020 to January 2021. A total of 86 patients undergoing surgery were assessed for eligibility, with 50 patients randomly assigned to the control group(received drilling and drainage) and 36 patients to the test group(received modified surgery). The six-month follow-up was done after surgery. CSDH recurrence and postoperative hematoma re-increasement were the primary endpoints. The data from the two groups were compared and analyzed. This study was registered with the Chinese Clinical Trials Register(ChiCTR2200057158), and had ethics committee approval and patient consent. Results: The incidence of PSP in the test group(0%, 0/30)was lower than the control group(93.88%, 46/49)(P<0.001). The brain non-expansion rates three days/weeks/months after surgery of the test group were 59.25 [49.62,76.97], 52.10 [42.88,72.45], and 29.45 [23.40,36.95] respectively, which were lower than the control group which were 78.60 [69.50,94.70], 73.10 [60.70,87.40], and 61.70 [51.50,78.30], respectively (P<0.001). The ADL scores a week/month/three months/six months after surgery of the test group were 100.00 [60.00,100.00], 100.00 [85.00,100.00], 100.00 [100.00,100.00], 100.00 [100.00,100.00], which were better than the control group's 60.00 [60.00,80.00], 75.00 [60.00,100.00], 100.00 [60.00,100.00], 100.00 [60.00,100.00](P<0.05). The incidence of primary endpoints in the test group (10%, 3/30) was lower than the control group (34.69%, 17/49) (P<0.05). Conclusions: Compared to drilling and drainage, the modified surgery with the active bone hole drainage system significantly reduced the incidence of PSP and primary endpoints and improved the postoperative efficacy and prognosis.